The microbiological diagnosis of Chlamydia trachomatis infections: milestones from a centenary history - Enrico Magliano (Microbiologia Medica, 2016)
August Compte, a French philosopher of science, back in the 18th Century wrote: You do not know a science, if you do not know its history. It is ambitious to adapt this aphorism to the history of the microbiological diagnosis of Chlamydia trachomatis infection, but the father of positivism would probably forgive me. [...]